PERAN KOMISI PEMILIHAN UMUM KABUPATEN TANAH DATAR DALAM SOSIALISASI POLITIK PADA PEMILIHAN UMUM LEGISLATIF 2019 - Devin Nofia; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The success of the election is influenced by how much public participation is in the election process. To increase community participation can be realized through political socialization. This outreach is one of the duties of the General Election Commission (KPU). The participation of the people of Tanah Datar Regency in the last 2019 legislative election experienced a significant increase compared to the previous election, reaching 72%. In the previous election, public participation only reached 65%. This means that the participation of the people of Tanah Datar has increased by 7% compared to the previous election, namely the 2014 election. This increase in participation is certainly inseparable from the role of the KPU, which is carrying out socialization regarding the holding of elections to the public. The purpose of this study was to determine the KPU's role in political socialization to increase public participation in elections and to determine the KPU's internal and external constraints in carrying out socialization. This research uses a descriptive research type with a qualitative approach located at KPU Tanah Datar. Primary data sources were obtained from interviews, secondary data sources were obtained from documents related to the research topic. Data collection techniques obtained through interviews and documentation. The data analysis technique used is qualitative data analysis. The results showed that the role played by the Tanah Datar KPU in increasing community participation was carried out through outreach activities. In carrying out socialization activities, the KPU of Tanah Datar Regency pays attention to the factors that influence the socialization, namely the material, methods and actors in carrying out the socialization. In carrying out socialization activities, KPU has internal constraints, namely a lack of budget and limited means of transportation to carry out socialization. While the KPU's external constraints are the lack of public response to socialization activities and there are still people who are apathetic towards politics. Keywords : Socialization Materials, Socialization Actors, Socialization Methods